THE EMOTIONAL FACTORS THAT EVOKED FROM THE MOST SUCCESSFUL TOURISM VIRAL VIDEO ADS - Cuaca, Philip; Iskandar, Budi Permadi (Journal of Business and Management, 2018)
Abstract.Nowadays tourism sector in Indonesia has become mainstay for the government to increase their national economic growth. A lot of things have been done to promote tourism sector in Indonesia, one of them is uploded tourism video in YouTube. This effort was done in order to attract the tourist interest in visiting Indonesia but only some of the content that posted on YouTube gets desired attention and only a fraction can reach large audiences. This conditions probably because of the emotions and some others elements does match with the criteria of an effective Tourism video. To adopt the appropriate emotions for case of tourism video in Indonesia, this research aims to benchmark and analyze the video that most successful in YouTube. In this research, the data is collected qualitatively from YouTubeâ€™s comments. The sample will be taken from 2 most viral tourism video ads comments which is from Australia and Quebec. Data will be validated using triangulation from 3 other researcher that has the same field and understanding to 25 emotions theory from Desmet in 2012. As a conclusion, this research found that the most frequent emotions from Most successful viral video was â€œRespectâ€, â€œAdmirationâ€, â€œDesireâ€, and â€Surpriseâ€. The other findings is Celebrity presence doesnâ€™t have a significant contribution to the success of the tourism video. The comparison of two approach are described further in the research. The result should be important and fascinated for other tourism video ads maker to produce an effective tourism video. Therefore a tourism video must consider the elements above to attract more audience and archive their goals.Keywords: Youtube, Tourism Ads, Tourism Video, Emotion Evoked, ViralityÂ Â Â